Effectiveness of teaching student teachers using E-Learning during COVID-19: A glance at inclusive education from the Zambian perspective - Kumatongo, Brighton; Mwansa, Patricia; Mweemba, Gibson (S&Co Publishing, 2023)
The use of technology as an alternative to traditional teaching during pandemics such as COVID-19 is attracting attention globally. This study sought to explore the effectiveness of teaching student teachers using E-Learning during COVID-19. Hearing students were learning together with students with hearing impairments in an inclusive environment before the closure of an institution. A mixed approach involving concurrent design was used and 193 student teachers who were purposively sampled from Kitwe College of Education in Zambia participated in the study, of which 4 of the participants were hearing impaired. The findings were that 53.9% of the participants had access to e-learning services, whereas 48.1 % had no. The study also revealed that 86% of the participants disagreed to having benefited from e-learning and cited lack of technological devices, poor network and expenses to purchase internet bundles as some of the barriers to e-learning. The study concluded that despite 53.9% of the participants having access to e-learning, 86% of the participants did not benefit from the use e-learning, due to lack of access to internet and expenses to purchase internet bundles, and that students with hearing impairments were disadvantaged due to lack of text and sign language interpretation during e-learning lectures. The study recommended the need to provide free internet bundles to students if e-learning is to be effective, educators record lessons and enable students to access, as well as need to consider students with hearing impairments during inclusive e-learning by providing sign language interpretation and texts.